2‐hydroxyethilammonium oleate protic ionic liquid as corrosion inhibitor for aluminum in neutral medium. Issue 3 (31st August 2020) - Ortega Vega, Maria R.; Mattedi, Silvana; Schroeder, Roberto M.; de Fraga Malfatti, Célia
Abstract: Protic ionic liquid (PIL) 2‐hydroxyethylammonium oleate (2HEAOl) proved to be a good lubricant for aluminum‐forming processes. However, with the aim of keeping the formed component integrity, it is interesting that the same substance employed during forming does not need to be removed and works out as corrosion inhibitor. Then, the aim of this study was to test the performance of 2HEAOl as corrosion inhibitor for aluminum in neutral 0.5 mol/L NaCl medium by electrochemical characterization. Results showed that the concentration of 5 × 10 −4  mol/L was a suitable concentration to promote corrosion inhibition until 72 h at the high chloride concentration studied. The PIL worked out as mixed‐type organic corrosion inhibitor, as it promoted the diminution of the oxygen reduction reaction rate and, in consequence, the pit initiation by its adsorption on the metal surface. Abstract : The aim of this study was to test the performance of 2HEAOl as corrosion inhibitor for aluminum in neutral 0.5 mol/L NaCl medium by electrochemical characterization. Results showed that the concentration of 5 × 10 −4  mol/L was a suitable concentration to promote corrosion inhibition until 72 hr at the high chloride concentration studied. The PIL worked as mixed‐type organic corrosion inhibitor.